2010
DOI: 10.1007/s10803-010-1118-4
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Children and Adolescents with ASD: Prevalence and Risk Factors

Abstract: The prevalence of and risk factors for aggression were examined in 1,380 children and adolescents with autism spectrum disorders (ASD). Prevalence was high, with parents reporting that 68% had demonstrated aggression to a caregiver and 49% to non-caregivers. Overall, aggression was not associated with clinician observed severity of ASD symptoms, intellectual functioning, gender, marital status, parental educational level, or aspects of communication. Individuals who are younger, come from a higher income famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
263
7
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(287 citation statements)
references
References 55 publications
11
263
7
6
Order By: Relevance
“…A broader study shows that in more than 50% of ASDs, physical aggression is seen as a snapshot of clinical finding, while 70% stated that aggression against caregivers was observed in their life span [32,33]. Many studies in ASDs have emphasized that there is no change in the level of aggression with age [31,[32][33][34]. Aggression has a clear relationship with HTR1E.…”
Section: Discussionmentioning
confidence: 99%
“…A broader study shows that in more than 50% of ASDs, physical aggression is seen as a snapshot of clinical finding, while 70% stated that aggression against caregivers was observed in their life span [32,33]. Many studies in ASDs have emphasized that there is no change in the level of aggression with age [31,[32][33][34]. Aggression has a clear relationship with HTR1E.…”
Section: Discussionmentioning
confidence: 99%
“…Although not inherent to the condition, anger is a clinically significant issue for many individuals with ASD and their families, with research indicating it is particularly problematic for adolescent males with ASD (Hodgetts, Nicholas, & Zwaigenbaum, 2013;Kanne & Mazurek, 2011;Mazurek, Kanne, & Wodka, 2013). For example, two large-scale studies investigating the experiences of anger in children and adolescents with ASD have found that over half display significant physical aggression (Kanne & Mazurek, 2011;Mazurek et al, 2013).…”
Section: Challenges Of Pubertymentioning
confidence: 99%
“…Although not inherent to the condition, anger is a clinically significant issue for many individuals with ASD and their families, with research indicating it is particularly problematic for adolescent males with ASD (Hodgetts, Nicholas, & Zwaigenbaum, 2013;Kanne & Mazurek, 2011;Mazurek, Kanne, & Wodka, 2013). For example, two large-scale studies investigating the experiences of anger in children and adolescents with ASD have found that over half display significant physical aggression (Kanne & Mazurek, 2011;Mazurek et al, 2013). Although the predictors of anger in individuals with ASD are not well understood, it has been suggested that it may stem from the frustration of feeling different and isolated from their peers (Barnhill & Myles, 2001; Levesque, 2011;Nasir & Tahir, 2012), their difficulties with communication (Simpson & Myles, 1998), and from coping with a range of often co-occurring challenges such as sleep problems and sensory abnormalities (Mazurek et al, 2013).…”
Section: Challenges Of Pubertymentioning
confidence: 99%
“…Indeed, rather than the diagnosis itself, aggressive behaviour associated with ASD is the greater source of distress for parents, often resulting in property damage as well as injury to self and others (Lecavalier et al 2006). Correspondingly, aggression is the main cause for concern expressed by teaching staff of children with ASD (Kanne and Mazurek 2011;Lecavalier et al 2006). Whilst the effects of aggression on parents has been widely evaluated in the domain of younger children and adolescents with ASD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Self-injurious behaviours, aggression towards others and the destruction of property are the most common types of aggression displayed by individuals with ASD (Kanne and Mazurek 2011;Mandell 2008). The literature investigating this phenomenon has become more prolific in recent years as researchers try to identify the link between ASD and aggression, particularly what contributes to and predicts such behaviours (e.g.…”
Section: Introductionmentioning
confidence: 99%